Epidemiology of Marssonina blotch (Marssonina coronaria) of apple in India - and SANJEEV SHARMA, NIRUPMA SHARMA, V.S. THAKUR*, J. MOHAN, S.M. PAUL KHURANA (Indian Phytopathology, 2009)
Between six levels of temperature and relative humidity, temperature of 200 C and 100% relative humidity were optimal for the conidial germination of Marssonina coronaria. The maximum relative rate of conidial germination occurred at 200 C and 100% relative humidity during 24 hours of incubation. The initiation of disease at lower temperature took place at 8h of leaf wetness while at temperature (20 and 25o C), it started only after 4h of leaf wetness. However, for the development of epidemic situation, a minimum of 40 h of leaf wetness was required. Studies revealed that the fungus overwintered on the infected fallen leaves in the form of acervuli and remained viable till the next season. The number of acervuli increased till 8 months of storage and maximum number and large sized acervuli produced under laboratory conditions. Temperature and relative humidity adversely affected viability of the fungus and coefficient of multiple determination indicated that 54.53 and 37.38 % variation in acervuli production and 80.74 and 80.08 % variations in conidial germination, respectively under orchard and laboratory conditions could be ascribed to these factors.